The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0886260517698703
|View full text |Cite
|
Sign up to set email alerts
|

Spoil the Rod and Save the Child: Socioeconomic Predictors of Harsh Discipline by Parents, Egyptian Case Study

Abstract: The purpose of this article is to investigate the use of harsh disciplinary methods by parents as corrective techniques for their children, and the resulting behavioral aspects in the affected children. Sociodemographic predictors are tested for estimating the impact of harsh disciplining by parents. A primary survey of a sample of 1,751 children 10 to 12 years of age across 12 provinces of Assiut Governorate in Egypt is considered. The analysis is carried out using exploratory factor analysis and confirmatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The present study findings showed that that more than two fifth of the mothers had mal-disciplinary adopted strategy with higher mean 67.59 ± 8.93 for authoritarian (verbal hostility, corporal punishment and non-reasoning strategies). This is with accordance to Mohammed and Samak [15] results who studied the disciplinary actions in upper Egypt and found that harsh discipline is evidential in all the studied sample of children. The second disciplinary strategy adopted by mothers in this study was authoritative These findings goes on with those of Cyril, Halliday, Green, and Renzaho [16]as in their study of relationship between body mass index and parenting style, the authoritative parenting style was the second most frequently used style by parents of children in the study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present study findings showed that that more than two fifth of the mothers had mal-disciplinary adopted strategy with higher mean 67.59 ± 8.93 for authoritarian (verbal hostility, corporal punishment and non-reasoning strategies). This is with accordance to Mohammed and Samak [15] results who studied the disciplinary actions in upper Egypt and found that harsh discipline is evidential in all the studied sample of children. The second disciplinary strategy adopted by mothers in this study was authoritative These findings goes on with those of Cyril, Halliday, Green, and Renzaho [16]as in their study of relationship between body mass index and parenting style, the authoritative parenting style was the second most frequently used style by parents of children in the study.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to that, Mohammed, and Samak [15] highlighted the strong significant correlation found between the harsh discipline of upper Egyptian children and their parents' age, level of education, income, and marital status. However, Socolar, Savage and Evans [22] concluded that the incidence of corporal punishment peaks when the age of the child is 4 to 8 years old.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…According to Elghossain et al [6], Egypt had the highest rate of CM in the Arab region (91%). The deep-rooted cultural model of parental discipline, which includes physically chastising and yelling, legitimizes the use of violence against children [7]. According to the latest nationally representative population survey in Egypt, 93% of children between ages 1 and 14 were exposed to violent disciplinary practices at some point during their childhood.…”
Section: Contextualizing Child Maltreatmentmentioning
confidence: 99%